OPERAÇÃO EM EMERGÊNCIA DE TRANSFORMADORES DE POTÊNCIA CONSIDERANDO RISCOS E CONTRATOS DE INTERRUPÇÃO. - SOUSA, Jéssica Cristina da Silva (2017)
As a result of a contingency, severe overloads may occur in a power transformer. One of the greatest concerns of energy utilities is to find a way to operate this equipment that ensures its useful life is preserved. However, there is a sharp reduction in the useful life in proportion to the level of overload and this increases the risk of failure. This paper sets out a framework for decision-making in emergency operations for power transformers, that rely on interruption contracts as decision variables and which take into account the risk of accepting any level of violation of the transformer´s operating limits. The risk of failure is calculated by measuring the useful life of the transformer and the presence of dissolved gases. The useful life is estimated by means of the Arrhenius model of thermal damage , while incipient faults can be detected by Dissolved Gas Analysis (DGA). The risk of transformer failure is estimated by examining the data cited above, on the basis of information theory concepts. It is formulated as a multi-period optimization problem with linear objectives and nonlinear constraints and restricted to the risk of accepting transformer overloads. The results are validated by means of an adapted version of the IEEE14 system, which is shown to be effective as a tool for emergency decision-making in the case studies included here.